Educational psychology : windows on classrooms - Eggen, Paul D. , 1940-; Kauchak, Donald P. , 1946- (Boston, Massachusetts : Peason, 2013)
Educational Psychology: Windows on Classrooms, Ninth Edition, will help you increase student learning and development. It is the most applied book in the field. If you're looking for a book that gives you a sound theoretical and research-based foundation and then provides specific and concrete illustrations and guidelines for applying this theory and research with your students, this is the book for you
1. Educational psychology : understanding learning and teaching -- 2. Cognitive and language development -- 3. Personal, social, and moral development -- 4. Learner diversity -- 5. Learners with exceptionalities -- 6. Principles of cognitive learning theory and the construction of knowledge -- 7. Cognitive learning and human memory -- 8. Complex cognitive processes -- 9. Behaviorism and social cognitive theory -- 10. Motivation and learning -- 11. A classroom model for promoting student motivation -- 12. Classroom management : developing self-regulated learners -- 13. Learning and effective teaching -- 14. Increasing learning through assessment -- 15. Standardized testing and learning
Includes bibliographical references and index
Keywords: Educational psychology -- Study and teaching (higher) -- United States; Learning, psychology of -- Case studies